Endemic insects from the Yungas of Argentina - Cuezzo, Fabiana; de Grosso, Mercedes Lizarralde; Navarro, Fernando; Szumik, Claudia (Zootaxa, 2007)
Until now, biogeographic unit of the Yungas was almost exclusively characterized by its floristic taxa. Presence of other taxonomical groups, in this case arthropods, were poorly recorded besides implicit mention of arthropods to characterizeYungas as a natural region. We present herein a species checklist of the holometabolous insects considered as endemics of the Yungas in Argentina. This checklist is a result of a rigorous endemicity analysis (Navarro et al, en prep.) Comments about altitudinal gradients of distribution for these endemic species are made. Results reveal a total of 23 endemic insects species of Yungas, representing 13 families of Lepidoptera, Diptera and Hymenoptera。